Особенности динамики подвижной системы электромагнитного вибростенда - Божко, А.Е.; Пушня, В.А. (Видавничий дім "Академперіодика" НАН України, 2007)
The peculiarities of the motion of the traveling system of an electromagnetical bench under the conditions of different dispositions of the inertia center and the main center of system's hard elements are shown.